(untitled) (Revista de História Regional, 2007)
This article pretends to understand the degree of participation of the municipal council of Rio de Janeiro, the main local power agency, in the discussion and design of proposals for the question of urban popular housing throughout the period of 1892 to 1902. The reflections on this subject are threefold. First, the key for understanding is a survey on scientific contributions from historians and other researchers, since 1980, on the question of urban popular housing in a kind of historiographic balance. The second and third moment are complementary and try to describe the existing negotiations and discussions between the Council members at the moment when legislative projects on cortiços and the construction of workers’ vilas were discussed.